App para el control de asistencia de estudiantes registrados en cursos de Moodle utilizando realidad aumentada (RA): caso de estudio UAN sede Sur (2025)
For a long time, the Antonio Nariño University has had a traditional mechanism for taking attendance, which is why the development of a mobile application for taking attendance using Augmented Reality (AR) will provide significant help to the professors of the institution. Once implemented they will no longer have to keep taking attendance on a sheet that has the list of students and verifying whether students are present or not. The main objective of this project is to use new technologies such as the QR Code and provide the university with better alternatives for its constant improvement and quality